Acne na mulher adulta: um impacto hormonal - Ferrari, Roberta Martins (My University, 2025)
Adult female acne is a multifactorial dermatological condition that affects a growing number of women over the age of 25 and can impact self-esteem, self-confidence, and quality of life. Among the main etiological factors, hormonal imbalances stand out, with emphasis on hyperandrogenism and other associated conditions, such as chronic stress and hormonal fluctuations throughout the menstrual cycle. This work consists of a literature review, with an exploratory and integrative character, whose main objective was to gather and analyze studies on adult female acne, focusing on the main associated factors, with emphasis on hormonal, laboratory aspects and the main indicated treatments. Studies published between 2015 and 2025 that addressed the descriptors and inclusion criteria were selected. The results indicate that laboratory evaluation, combined with clinical analysis and associated signs, is essential to guide an individualized and effective treatment plan. In addition, aesthetic procedures such as skin cleansing and chemical peels, combined with home care and pharmacological treatments, show excellent response to treatment. It is concluded that the biomedical professional plays a crucial role, acting in an interdisciplinary manner to promote health and quality of life for patients affected by this condition. [resumo fornecido pelo autor]
A acne na mulher adulta é uma condição dermatológica de origem multifatorial que acomete um número crescente de mulheres acima dos 25 anos, e que pode afetar a autoestima, a autoconfiança e a qualidade de vida. Dentre os principais fatores etiológicos, destaca-se os desequilíbrios hormonais, com ênfase no hiperandrogenismo e demais condições associadas, como estresse crônico e variações hormonais ao longo do ciclo menstrual. Este trabalho consiste em uma revisão de literatura, de caráter exploratório e integrativo, cujo principal objetivo foi o de reunir e analisar estudos sobre a acne na mulher adulta com abordagem nos principais fatores associados, com enfoque nos aspectos hormonais, laboratoriais e principais tratamentos indicados. Foram selecionados estudos publicados entre 2015 e 2025 que abordam os descritores e critérios de inclusão. Os resultados apontam que a avaliação laboratorial, aliada a análise clínica e sinais associados, é essencial para direcionar um plano de tratamento individualizado e eficaz. Além disso, os procedimentos estéticos, como limpeza de pele e peelings químicos, somados a cuidados domiciliares (home care) e tratamentos farmacológicos, apresentam uma excelente resposta ao tratamento. Conclui-se que o biomédico possui papel crucial, atuando de forma interdisciplinar para promover saúde e qualidade de vida às pacientes acometidas por essa condição. [resumo fornecido pelo autor]
Keywords: Acne - Mulheres; Hormônios - Mulheres